Role of the Extracellular Matrix in Loss of Muscle Force With Age and Unloading Using Magnetic Resonance Imaging, Biochemical Analysis, and Computational Models - Sinha, Usha; Malis, Vadim; Chen, Jiun-Shyan; Csapo, Robert; Kinugasa, Ryuta; Narici, Marco Vincenzo; Sinha, Shantanu (Frontiers in Physiology, 2020)
The focus of this review is the application of advanced Magnetic Resonance Imaging (MRI) to study the effect of aging and disuse related remodeling of the extracellular matrix (ECM) on force transmission in the human musculoskeletal system. Structural MRI includes (i) ultralow TE maps to visualize and quantify the connective tissue, (ii) DTI modeling to estimate changes in muscle and ECM microstructure, and (iii) magnetization transfer contrast imaging to quantify the macromolecular fraction in muscle. Functional MRI includes dynamic acquisitions during contraction cycles enabling computation of the strain tensor to monitor muscle deformation. Further, shear strain extracted from the strain tensor may be a potential surrogate marker of lateral transmission of force. Biochemical and histological analysis of muscle biopsy samples can provide “gold-standard” validation of some of the MR findings. The review summarizes biochemical studies of ECM adaptations with age and with disuse. A brief summary of animal models is included as they provide experimental confirmation of longitudinal and lateral force transmission pathways. Computational muscle models enable exploration of force generation and force pathways and elucidate the link between structural adaptations and functional consequences. MR image findings integrated in a computational model can explain and predict subject specific functional changes to structural adaptations. Future work includes development and validation of MR imaging biomarkers using biochemical analysis of muscle tissue as a reference standard and potential translation of the imaging markers to the clinic to non-invasively monitor musculoskeletal disease conditions and changes consequent to rehabilitative interventions.